Beauty and Body dissatisfaction experienced by young Indian women exposed to foreign print advertisements found in International fashion Magazines targeted at women. - Batra, Radhika (2007)
This dissertation has been greatly concerned with the impact of the advertising images in international mass media, mainly womenÃ¢ÂÂs fashion magazines. Three advertisements, two from Cosmopolitan and one from Elle magazine, United Kingdom were used in order to test the impact of beauty and body image concerns in young Indian women. Literature has mainly concentrated on the portrayal of white women as advertising and cultural stereotypes in a global environment. Many studies have revealed that culture plays a very vital role in the way advertising and the visuals of women in them are perceived in society. Beauty has been always associated with superiority and global appreciation. Whiteness in particular is considered to be GodÃ¢ÂÂs gift to mankind and non white women are considered to be unwanted elements of society. However today trends are changing and even though women from the West are considered dynamically beautiful, advertising industry is also getting more and more appreciative of Asian beauty in international advertisements for cosmetic products. Body image is also one more important dimension that is explored in this dissertation and there is a general perception that fatness is associated with being ugly and since a very young age girls are affected by the discrepancies between their body image and the cultural body image. Thus body dissatisfaction is a very important concept that seems to be a concern of every young woman irrespective of ethnic origin. The objective of this study has been to understand these sensitive and personal issues from the eyes of young Indian women who are active members of this global environment and well versed with international fashion magazines.